2019
DOI: 10.1016/j.abrep.2018.100145
|View full text |Cite
|
Sign up to set email alerts
|

Cultural socialization and alcohol use: The mediating role of alcohol expectancies among racial/ethnic minority youth

Abstract: Introduction Cultural socialization is associated with reduced risk for several health outcomes among racial/ethnic minority youth. However, to date, less is known about its effect on substance use or the mechanisms through which this process may operate. The current study aimed to examine the effect of cultural socialization on alcohol use through alcohol expectancies among racial/ethnic minority youth. Methods 113 minority adolescents (69.9% African American; 13.3% Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…It shows that ERS can buffer the effect of discrimination (Carranza 2007;Ayón 2016). It also shows that ERS is related to ethnic identity development (Quintana and Vera 1999;Hughes et al 2009;Rivas-Drake et al 2009;Knight et al 2011Knight et al , 2017Umaña-Taylor 2015, 2016;Else-Quest and Morse 2015;White et al 2018;Christophe et al 2019;Wang et al 2019), academic adjustment (Huynh and Fuligni 2008;Berkel et al 2010;Calzada et al 2012;McGill et al 2012;Umaña-Taylor et al 2014;Caughy and Owen 2015;Rivas-Drake and Marchand 2016;Kim et al 2018;McDermott et al 2018), mental health (Phinney and Chavira 1995;Derlan et al 2015;Espinoza et al 2016;Padilla et al 2016;Santiago et al 2016;Wang and Benner 2016;Gonzales-Backen et al 2017;Chen et al 2019;Park et al 2019), and behavioral health (Grindal and Nieri 2016;Nieri et al 2019;Zapolski and Clifton 2019).…”
Section: Findings Of Existing Researchmentioning
confidence: 92%
See 1 more Smart Citation
“…It shows that ERS can buffer the effect of discrimination (Carranza 2007;Ayón 2016). It also shows that ERS is related to ethnic identity development (Quintana and Vera 1999;Hughes et al 2009;Rivas-Drake et al 2009;Knight et al 2011Knight et al , 2017Umaña-Taylor 2015, 2016;Else-Quest and Morse 2015;White et al 2018;Christophe et al 2019;Wang et al 2019), academic adjustment (Huynh and Fuligni 2008;Berkel et al 2010;Calzada et al 2012;McGill et al 2012;Umaña-Taylor et al 2014;Caughy and Owen 2015;Rivas-Drake and Marchand 2016;Kim et al 2018;McDermott et al 2018), mental health (Phinney and Chavira 1995;Derlan et al 2015;Espinoza et al 2016;Padilla et al 2016;Santiago et al 2016;Wang and Benner 2016;Gonzales-Backen et al 2017;Chen et al 2019;Park et al 2019), and behavioral health (Grindal and Nieri 2016;Nieri et al 2019;Zapolski and Clifton 2019).…”
Section: Findings Of Existing Researchmentioning
confidence: 92%
“…Cultural socialization was associated with less substance use, and preparation for bias was associated with more substance use. The final study was crosssectional and examined the relationship between cultural socialization, positive and negative alcohol expectations, and substance use (Zapolski and Clifton 2019). The authors found support for an indirect effect of cultural socialization on substance use through negative alcohol expectations.…”
Section: Ers and Mental And Behavioral Healthmentioning
confidence: 99%
“…67 Another study showed that family-based cultural socialization, in which family members teach adolescents about the importance of their ethnic/cultural background, increased minority adolescents’ negative arousal expectancies about alcohol, which in turn was associated with reductions in their consumption. 68 Our results suggest that minority youth with distorted alcohol expectancies and externalizing behaviors are at-risk for clinically severe alcohol use and may benefit from intervention programs designed to decrease both of these risk factors. Brief intervention programming incorporating challenges to distorted cognitions may be particularly efficacious.…”
Section: Discussionmentioning
confidence: 72%
“…Their level of control determines their thoughts and beliefs regarding when and how much they consume. Zapolski and Clift [ 15 ] reported that cultural socialization decreased the risk of alcohol consumption indirectly through alcohol expectancies among racial minority adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…These lower levels of alcohol consumption among HBCU students could be connected to high scores on racial/ethnic identity and resiliency. Similarly, Zapolski and Clift [ 15 ] suggest that cultural socialization may decrease the risk of alcohol consumption among racial/ethnic minority youth. Other studies hypothesized that drinking frequency and quantity could be predicted by knowledge of alcohol expectancies [ 16 , 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%